The High Cost of Politics in Indonesia: An Exploration of Multiperspectives from Academics, Students, Executive Officials, and Legislative Candidates - Darmawan, I Made Dwi Hita (Bestuurskunde: Journal of Governmental Studies, 2024)
The issue of high electoral political costs in Indonesia has been a serious concern since the 1998 reforms. This study aims to explore the factors that contribute to the high political costs in Indonesia’s democratic electoral system. The research question posed is: “What are the factors that lead to high political costs in Indonesia’s democratic electoral system?” The study employs a qualitative method with an in-depth interview approach. The informants for this study included academics, students, executive officials, and legislative candidates, selected to explore perspectives from various levels of society and the state. The selection of these informants was based on their diverse backgrounds, which were considered capable of providing comprehensive views on this issue. The findings reveal that the high cost of politics is caused by several factors, including an unusual electoral system, a paradigm shift in political parties, the prioritization of popularity over competence, campaign finance sponsorship, payback politics, and the phenomenon of “dawn raids.” The conclusion of this study indicates that the high cost of politics is a complex problem that requires a cross-sectoral approach to find a solution. The implication of this study is the importance of a deeper analysis of the mechanisms of political financing and their impact on democracy in Indonesia. This study makes an important contribution to understanding and addressing the problem of electoral political costs in Indonesia and emphasizes the need for cross-sectoral cooperation to achieve sustainable solutions.